Pengaruh Employee Retention dan Stress Kerja Terhadap Kinerja Karyawan PT. Multistrada Arah Sarana - Nandang Nandang; Asep Jamaludin; Mardiansyah Fajar (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to see the differences in the results of the influence of employee retention and work stress on employee performance in various organizations and industrial sectors. In this study, quantitative methods were used to examine employee retention and work stress that affect employee performance at PT Multistrada Arah Sarana. The population in this study were employees of PT Multistrada, while the sample taken was 86 respondents who were randomly selected using accidental sampling. In this study, data analysis used multiple regression method den R square. This study concludes that employee retention has a positive effect on employee performance, and work stress is proven to have a negative impact on employee performance. R square or the coefficient of determination in Table 8 produces a value of 0.376. This figure implies that the independent variable has an impact of 37.6% on the dependent variable, with the remaining 62.4% being influenced by other factors. Keywords: Employee Performance, Employee Relations, Turnover